Correlations between age, kinematics, and chemistry as seen by the RAVE survey. Issue 4 (24th April 2018) - Wojno, Jennifer; Kordopatis, Georges; Steinmetz, Matthias; McMillan, Paul; Binney, James; Famaey, Benoit; Monari, Giacomo; Minchev, Ivan; Wyse, Rosemary F G; Antoja, Teresa; Siebert, Arnaud; Carrillo, Ismael; et al.
Abstract: We explore the connections between stellar age, chemistry, and kinematics across a Galactocentric distance of 7.5 < R (kpc) < 9.0, using a sample of ∼12 000 intermediate-mass (FGK) turn-off stars observed with the RAdial Velocity Experiment (RAVE) survey. The kinematics of this sample are determined using radial velocity measurements from RAVE, and parallax and proper motion measurements from the Tycho–Gaia Astrometric Solution (TGAS). In addition, ages for RAVE stars are determined using a Bayesian method, taking TGAS parallaxes as a prior. We divide our sample into young (0 < τ < 3 Gyr) and old (8 < τ < 13 Gyr) populations, and then consider different metallicity bins for each of these age groups. We find significant differences in kinematic trends of young and old, metal-poor and metal-rich, stellar populations. In particular, we find a strong metallicity dependence in the mean Galactocentric radial velocity as a function of radius ( V_R/ R ) for young stars, with metal-rich stars having a much steeper gradient than metal-poor stars. For V_φ / R, young, metal-rich stars significantly lag the LSR with a slightly positive gradient, while metal-poor stars show a negative gradient above the LSR. We interpret these findings as correlations between metallicity and the relative contributions of the non-axisymmetries in the Galactic gravitational potential (the spiral arms and the bar) to perturb stellar orbits.